A 5‐year longitudinal study of association of maximum bite force with development of frailty in community‐dwelling older adults. (13th October 2017) - Iwasaki, M.; Yoshihara, A.; Sato, N.; Sato, M.; Minagawa, K.; Shimada, M.; Nishimuta, M.; Ansai, T.; Yoshitake, Y.; Ono, T.; Miyazaki, H.
Summary: To determine whether maximum bite force (MBF), an objective measure of oral function, is associated with development of frailty in community‐dwelling older adults. This prospective cohort study included community‐dwelling Japanese adults aged 75 years at baseline (n = 322). Baseline MBF was measured using an electronic recording device (Occlusal Force‐Meter GM10). Follow‐up examinations, including physical fitness and anthropometric evaluation and structured questionnaires, were administered annually over a 5‐year period to determine the incidence of frailty, which was defined by the presence of 3 or more of the following 5 components derived from the Cardiovascular Health Study: low level of mobility, low physical activity level, weakness, shrinking and poor endurance and energy. Adjusted hazard ratios (HRs) of incidence of frailty according to sex‐stratified tertiles of baseline MBF were calculated using Cox proportional hazards regression models. During the follow‐up, 49 participants (15.2%) developed frailty. Participants in the lower tertile of MBF exhibited a significantly greater risk of frailty than those in the upper tertile. After adjustment for sex, depression, diabetes and Eichner index, the adjusted HRs for frailty in the upper through lower tertiles of MBF were 1.00 (reference), 1.27 (95% confidence interval [CI]: 0.50‐3.20) and 2.78 (95% CI: 1.15‐6.72), respectively ( P for trend = .01). Poor oral function, as indicated by low MBF, increases the risk of development of frailty among elderly men and women.